A broader palate? The new and exotic food experiences of the Australian imperial force 1914–1918. Issue 2 (26th April 2021) - Reynaud, Daniel; Reynaud, Emanuela
Abstract: This article explores the new food experiences of the Australian Imperial Force (AIF) during the First World War, drawing evidence from scholarly works, archives and soldier accounts. Having come from a predominantly British food culture in Australia, the AIF encountered new tastes and eating habits in the Middle East and Europe, which they experienced in dual roles as soldiers and tourists. Some soldiers responded warmly while others reacted defensively to these new foodways such as self-catering, exotic ingredients and dishes, regular dining out and new food customs. The lack of long-term impact of these novel experiences on Australian foodways is also noted.